Implementasi Program Pelayanan Perlindungan dan Rehabilitasi Anak Nakal di Kota Surabaya - Deliar Syaifuddin; Sri Roekminiati; Amirul Mustofah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This research aims to analyze the implementation of the Protection and Rehabilitation Service Program for Juvenile Delinquents in Surabaya City, conducted by the Social Service of East Java Province. Juvenile delinquency remains a significant social problem requiring comprehensive intervention through protection and rehabilitation approaches rather than punitive measures. Drawing on George C. Edward III's policy implementation theory, this study examines four critical factors: communication, resources, disposition, and bureaucratic structure. This qualitative research employs a descriptive approach, with data collected through in-depth interviews, observation, and documentation at the Social Service of East Java Province during June-August 2025. Informants include program managers, social workers, psychologists, beneficiaries of the juvenile delinquency program, and their families. The results indicate that the program has successfully served 1,247 juvenile delinquents through integrated services, including psychological counseling, skills training, family therapy, and social reintegration support. The communication dimension shows effective coordination between provincial and city-level agencies, though information dissemination to communities needs improvement. Resource adequacy is generally sufficient with 35 certified social workers, adequate facilities, and an annual budget of Rp 3.2 billion. The disposition of implementers demonstrates a strong commitment to child-centered approaches. Clear SOPs and inter-agency collaboration protocols support the bureaucratic structure. The program achieves 72% successful rehabilitation rate with 68% of beneficiaries returning to formal education or productive activities. Challenges remain in stigma reduction, family involvement, and post-rehabilitation monitoring. This study recommends strengthening community-based prevention, expanding vocational training options, developing peer support networks, and establishing sustainable aftercare mechanisms.